2018
DOI: 10.1007/s11524-018-0280-4
|View full text |Cite
|
Sign up to set email alerts
|

Public Housing on the Periphery: Vulnerable Residents and Depleted Resilience Reserves post-Hurricane Sandy

Abstract: Hurricane Sandy was the greatest natural disaster to ever impact public housing residents in New York City. It affected approximately 80,000 residents in 400 buildings in 33 developments throughout the city. The storm left residents without power, heat, or running water, yet many chose not to evacuate. This qualitative study was conducted to understand the impact of Sandy among this socially, physically, and geographically vulnerable population. It is the first known study to examine the impact of disasters in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 43 publications
0
21
0
Order By: Relevance
“…Energy insecurity plays a role in depleting a person's resilience reserve (24). The resilience reserve framework offers a different lens than does past resilience research, which found that marginalized groups were less resilient because they had less social and material support and more life stressors (145).…”
Section: High-effort Coping and Resilience Reservesmentioning
confidence: 96%
See 4 more Smart Citations
“…Energy insecurity plays a role in depleting a person's resilience reserve (24). The resilience reserve framework offers a different lens than does past resilience research, which found that marginalized groups were less resilient because they had less social and material support and more life stressors (145).…”
Section: High-effort Coping and Resilience Reservesmentioning
confidence: 96%
“…The resilience reserve framework offers a different lens than does past resilience research, which found that marginalized groups were less resilient because they had less social and material support and more life stressors (145). The resilience reserve framework argues instead that marginalized groups that contend with social, economic, medical, physical, and geographic vulnerabilities expend resilience resources to manage everyday hardships, leaving less opportunity to accumulate the psychological and material means with which to respond to and recover from large shocks such as extreme climate events (24). Therefore, after a disaster, marginalized groups have greater difficulties coping and rebounding, because they have already depleted their reserves.…”
Section: High-effort Coping and Resilience Reservesmentioning
confidence: 98%
See 3 more Smart Citations